Influence of Parents' Economic and Educational Status on Children's Learning (Pragyaratna प्रज्ञारत्न, 2024)
Economic and educational status of parents directly and indirectly influences the children’s learning. This article explores Influence of Parents' Economic and Educational Status on Children's Learning. The study was conducted in Sudal area of Bhaktapur district where several people have migrated from several districts and have taken employment in several areas including brick factories. Qualitative research designed was used in this study. The population of the study included all head teachers, all teachers who taught in grade-3 and students of grade-3 at schools in Bhaktapur district and the parents working in the brick factories are population of this study. Out of this population, one school located in Chyamasing area was selected as a case. The study was further narrowed down to grade-3. This school’s head teacher, one teacher who taught in grade-3, one grade-3 student and one parent of same student who is working in brick factory was chosen purposively as sample in this case study. In this qualitative case study, in-depth interviews and observations were conducted to understand parental activities and behavior in supporting their children’s learning. This research concluded that not only economic and educational status of the parent’ influence children’s learning but also positive behavior of parents toward the children, good relationship between parents and children, good parenting style, ways of motivation of parents, and positive feedbacks of teacher, remedial teaching, proper support from teacher’s positively influenced their children’s learning.